Law and Social Symptoms in Enforcement of Community - Aufa, Muhammad Fikri (Multidiscience : Journal of Multidisciplinary Science, 2025)
Sociology cannot be directly used in distorting the scope of jurisprudence in terms of its independence, sociology of law is a middle way with various intersections. The complex reality in society gives many distortions whether the law can be independent or become a truly substantially open system, amidst the position of our legal development, which was previously the perspective of Dutch scientists and is currently required to accommodate “the laws that live in a society” So the role of legal sociology in law enforcement in society is very much needed. This research is qualitative descriptive research with the type of library research. The method used in this research is normative legal research methodology, which places law as a building block of ethical structures (namely regarding principles, ethics, regulations from statutory provisions, court decisions, agreements, and doctrine). In this research, the law is not an autonomous institution but is interdisciplinary in dealing with social phenomena to create social welfare. Law enforcement in society is an effort to realize respect for social norms. Through legal improvement, it must include preventive and repressive improvement stages, edit of morality, the behavior of law enforcement officials, and as an essential element is community involvement.